Enhancing EFL Learners’ Conjunction Proficiency in Recount Writing: An Analytical Study - Juhansar, Juhansar; Trihat Majaya, Brigas; Kamsinah, Kamsinah; Budiarti, Budiarti (ETERNAL (English, Teaching, Learning and Research Journal), 2023)
Although it seems straightforward, using conjunctions in recount text writing poses a serious challenge for Indonesian EFL learners who continue to use them incorrectly. This current research aims to identify and describe EFL learners’ types and causes of conjunction errors in writing recount texts. This research relays on a mixed-methods research design where 27 participants were 10th-grade EFL learners of SMK Muhammadiyah Berbah in the 2022/2023 academic year. Data were collected through documents and interviews. The collected data were analyzed both qualitatively and quantitatively. Qualitative analysis was used to discover EFL learners' types and causes of conjunction errors in writing recount text. In contrast, quantitative analysis was used to present the number and percentage of EFL learners' errors. This research shows that EFL learners make four types of errors in using conjunctions to write recount text. The types of errors consist of 55.81% omission errors, 23.25% unnecessary addition errors, 18.60% misuse errors, and 2.32% repetition errors. Ignorance of rule restrictions causes EFL learners to make errors of misuse, unnecessary addition, and excessive repetition. Meanwhile, the incomplete application of the rules caused EFL learners to make omission errors.